Severe developmental delay, epilepsy and neonatal diabetes (DEND) syndrome: a case report - Muhd Helmi, Muhd Alwi; Hussain, Suhaimi (ASEAN Federation of Endocrine Societies, 2020)
Developmental delay, Epilepsy and Neonatal Diabetes (DEND) syndrome is the most severe form of Permanent Neonatal Diabetes with KCNJ11 gene mutation which accounts for most of the cases. We report the first DEND syndrome in Malaysia with heterozygous missense mutation Q52R at KCNJ11 (Kir6.2) gene with delayed presentation beyond 6 months of age and failure to transition to glibenclamide. This report signifies the phenotypical variability among patients with the same genetic mutation and the different response to treatment.